Art is a combat discipline: George Grosz and Günther Anders (Itinera, 2021)
The essays on Aesthetics of philosopher Günther Anders are still almost unknown; for his part, painter George Grosz’ production from the 1930s and during his American exile has been mainly despised by art historians. Both Anders and Grosz considered themselves as holding up an unmerciful mirror to society. The aim of this paper is to offer an analysis on the short but poignant texts which Anders wrote on Grosz’ artistic research, providing some of the most vitriolic social criticism of his time. The studies of Anders show unpredicted connections, unveiling in an unprecedented way the deep unity of Grosz’ wide œuvre marked by an absolute pessimism, and therefore particularly near to the philosopher’s “negative ontology”. Moreover, these texts raise key questions concerning modern art itself which are still central in our time, among others: the political engagement of artists, their relationship with the market, and their clairvoyance, the ethical use of montage practice, and the thin line between life and art.
Keywords: George Grosz, Günther Anders, Man without World, World without Man